2020
DOI: 10.1128/mbio.03363-19
|View full text |Cite
|
Sign up to set email alerts
|

New Pathogenesis Mechanisms and Translational Leads Identified by Multidimensional Analysis of Necrotizing Myositis in Primates

Abstract: A fundamental goal of contemporary biomedical research is to understand the molecular basis of disease pathogenesis and exploit this information to develop targeted and more-effective therapies. Necrotizing myositis caused by the bacterial pathogen Streptococcus pyogenes is a devastating human infection with a high mortality rate and few successful therapeutic options. We used dual transcriptome sequencing (RNA-seq) to analyze the transcriptomes of S. pyogenes and host skeletal muscle recovered contemporaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 97 publications
1
18
0
Order By: Relevance
“…al,. including sagA, arcA, and the cellobiose PTS operon, were directly bound by CcpA in our study, all of which we classified as HPr-dependent. Conversely, the transcript levels of the directly CcpA bound, HPr-independent genes of the sialic acid operon, prtS, ackA, and hpr showed no significant upregulation during necrotizing fasciitis (Kachroo et al, 2020). These findings are consistent with the concept that CcpA can maintain repression of these genes even under metabolically unfavorable conditions when HPrSer46~P levels would be expected to be low.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…al,. including sagA, arcA, and the cellobiose PTS operon, were directly bound by CcpA in our study, all of which we classified as HPr-dependent. Conversely, the transcript levels of the directly CcpA bound, HPr-independent genes of the sialic acid operon, prtS, ackA, and hpr showed no significant upregulation during necrotizing fasciitis (Kachroo et al, 2020). These findings are consistent with the concept that CcpA can maintain repression of these genes even under metabolically unfavorable conditions when HPrSer46~P levels would be expected to be low.…”
Section: Discussionsupporting
confidence: 83%
“…The dependence/independence of CcpA from HPr~P could assist with fine-tuning regulation of pertinent genes by CcpA such that site specific resources can be utilized optimally to aid the pathogen. For example, a recent study compared the GAS transcriptome during necrotizing fasciitis to growth in standard laboratory medium (Kachroo et al, 2020). Some of the most highly upregulated genes in Kachroo et.…”
Section: Discussionmentioning
confidence: 99%
“…The polycistronic expression and upregulation of these genes in whole blood and during necrotizing myositis suggest that HitABC and Irr-Ihk might be functionally related. In line with this idea, we reported that hitABC and irr-ihk are both crucial for GAS virulence in an NHP model of necrotizing myositis (32,98). Because the Irr-Ihk TCS contributes to GAS's ability to resist being killed by neutrophils and neutrophil-derived antimicrobial peptides (72), further functional studies are needed to determine whether the HitABC transporter serves as an efflux pump for neutrophil-derived antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 85%
“…34 The Ihk/Irr two-component system is involved in the regulation of various streptococcal processes, including virulence. 35,36 It is notable that ihk/irr were overexpressed in a non-human primate model of GAS necrotizing myositis, and these genes were implicated in GAS resistance to polymorphonuclear phagocytosis. 36 The fact that CCCP inhibited ihk/irr gene regulators and the RND family operon concomitantly, and that both the operon and regulators displayed increased expression in GAS-persistent cells, raises an interesting hypothesis about another possible role for the Ihk/Irr system besides virulence regulation.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 It is notable that ihk/irr were overexpressed in a non-human primate model of GAS necrotizing myositis, and these genes were implicated in GAS resistance to polymorphonuclear phagocytosis. 36 The fact that CCCP inhibited ihk/irr gene regulators and the RND family operon concomitantly, and that both the operon and regulators displayed increased expression in GAS-persistent cells, raises an interesting hypothesis about another possible role for the Ihk/Irr system besides virulence regulation. However, despite the gene co-localization and the concomitant regulation of ihk/irr and the genes of the ABC transport operon by CCCP, molecular cloning strategies are needed to validate the hypothesis that ihk/irr may not only regulate GAS virulence but also this transport system.…”
Section: Discussionmentioning
confidence: 99%